Nocturnal respiratory rate predicts ICD benefit: A prospective, controlled, multicentre cohort study. (January 2021) - Dommasch, Michael; Steger, Alexander; Barthel, Petra; Huster, Katharina M; Müller, Alexander; Sinnecker, Daniel; Laugwitz, Karl-Ludwig; Penzel, Thomas; Lubinski, Andrzej; Flevari, Panagiota; Harden, Markus; Friede, Tim; et al.
Abstract: Background: Implantable cardioverter defibrillators (ICDs) prevent sudden cardiac death. ICD implantation decisions are currently based on reduced left ventricular ejection fraction (LVEF≤35%). However, in some patients, the non-arrhythmic death risk predominates thus diminishing ICD-therapy benefits. Based on previous observations, we tested the hypothesis that compared to the others, patients with nocturnal respiratory rate (NRR) ≥18 breaths per minute (brpm) benefit less from prophylactic ICD implantations. Methods: This prospective cohort study was a pre-defined sub-study of EU-CERT-ICD trial conducted at 44 centers in 15 EU countries between May 12, 2014, and September 6, 2018. Patients with ischaemic or non-ischaemic cardiomyopathy were included if meeting primary prophylactic ICD implantation criteria. The primary endpoint was all-cause mortality. NRR was assessed blindly from pre-implantation 24-hour Holters. Multivariable models and propensity stratification evaluated the interaction between NRR and the ICD mortality effect. This study is registered with ClinicalTrials.gov (NCT0206419). Findings: Of the 2, 247 EU-CERT-ICD patients, this sub-study included 1, 971 with complete records. In 1, 363 patients (61.7 (12) years; 244 women) an ICD was implanted; 608 patients (63.2 (12) years; 108 women) were treated conservatively. During a median 2.5-year follow-up, 202 (14.8%) and 95 (15.6%) patients died in the ICD and control groups, respectively. NRR statistically significantly interacted with the ICD mortality effect ( p  = 0.0070). While the 1, 316 patients with NRR<18 brpm showed a marked ICD benefit on mortality (adjusted HR 0.529 (95% CI 0.376–0.746); p  = 0.0003), no treatment effect was demonstrated in 655 patients with NRR≥18 brpm (adjusted HR 0.981 (95% CI 0.669–1.438); p  = 0.9202). Interpretation: In the EU-CERT-ICD trial, patients with NRR≥18 brpm showed limited benefit from primary prophylactic ICD implantation. Those with NRR<18 brpm benefitted substantially. Funding: European Community's 7th Framework Programme FP7/2007-2013 (602299)